Weld morphology, microstructure and mechanical property of laser welded joint of Ti80 alloy - Fei Yan; Jingrui Liu; Gao Liu; Panpan Lin; Zhongmei Gao; Pan Zhang; Xiaoyang Lu; Peng Jiang (Journal of Materials Research and Technology)
In this paper, we describe experimental laser welding of new-type Ti80 alloy (Ti–6Al–3Nb–2Zr–1Mo) under varying welding speeds. Weld morphology, microstructure and mechanical properties of laser welded joints were carefully investigated using optical microscope (OM), scanning electron microscope (SEM), electron back-scattered diffraction (EBSD) and other methodologies. The results demonstrated that high-quality laser-welded joints were successfully achieved at a welding speed of 40 mm/s, exhibiting a tensile strength of 894 MPa (98 % of base metal) and an elongation of 12 %. Rapid cooling during the welding process of 40 mm/s promoted the formation of acicular α′ martensite with a volume fraction of 99.5 %, refined the grain size to 3.3 μm and increased the hardness to 430 HV. EBSD analysis revealed that dynamic recrystallization (73.5 % recovered grains + 23.1 % DRX grains) dominated the weld zone (WZ), thus generating 96.2 % high-angle boundaries with an average grain size of 3.6 μm. The CDRX mechanism, quantified via kernel average misorientation (0.59°) and GND density (1.66 × 1014/m2), can enhance the strength but restrict the ductility. However, joint strength and elongation at a welding speed of 45 mm/s were reduced to 878 MPa and 5 % respectively due to porosity clustering and undercuts. Optimal properties at the welding speed 40 mm/s were mainly attributive to homogeneous α′ distribution and minimal defects (<0.5 vol%). The research results provide the theoretical basis and technical support for the high-quality and efficient welding of titanium alloy components in marine engineering and aerospace field.